The influence of land use on the spatial distribution and intensity of heat islands in Slovenia - Simčič, Anica (Acta silvae et ligni, 2021)
Heat islands (HI) are a common anthropogenic phenomenon and are defined as artificial surfaces (urban areas) that have a higher average temperature than their surroundings (rural areas). The aim of this work was to determine the influence of land use on the spatial distribution and intensity (HIi ) of HI in Slovenia. The MODIS Land Surface Temperature (LST) and Corine Land Cover (CLC) databases were used to perform the analysis. Within the identified HI, two HI levels were determined based on temperature difference. The results revealed a statistically significant negative correlation between HIi and both forest co%ver and forest fragmentation (forest edge density and ratio of mean forest patch size to HI size). Artificial surface was positively correlated with HIi . The results contribute to the understanding of the spatial distribution of HI and HIi and provide informati%on for spatial planning and policy-making to reduce the negative impact of HI.
Keywords: artificial surface; forest cover; forest fragmentation; fragmentiranost gozda; gozdnatost; heat island; toplotni otok; umetne površine